ANALISIS PERHITUNGAN KEBUTUHAN RAK DAN LUAS RUANG PENYIMPANAN DOKUMEN REKAM MEDIS DI RS PANTI WALUYA SAWAHAN MALANG - Yocky Sepvano Hananda (Health Care Media, 2023)
Storage of medical record documents is the process of storing and arranging medical record documents in order to make them easier to retrieve. The need for medical record racks is very influential in service delivery. Medical record racks that are in accordance with existing medical record documents will make the service run well. Based on a preliminary study conducted in February 2023, information was obtained that the storage system used was centralized and it was also known that the area of the DRM storage room was 9.6 m wide and 15 m long and contained 11 wooden model shelves with a length of 10 m and 1 m wide. The purpose of this study was to analyze the calculation of the need for DRM racks and storage space at Panti Waluya Sawahan Hospital, Malang. This study uses the IFHIMA calculation formula. This type of research uses descriptive research. The sample of this study was 225,067 medical record documents. The results of the study were 225,067 patient visits over the last 5 years and the average thickness of inpatient medical record documents was 2.9 cm and 0.73 cm outpatient. After calculating with the IFHIMA formula, the Waluya Sawahan Malang Panti Hospital still needs to add 8 shelves and a storage area of 69.09 m2 for 2023 – 2027. Keyword. IFHIMA, Calculation of medical record shelves, Calculation of filing